The Legal Protection for Workers Who Exceed the Overtime Limit Based on the Labor Law - Pohan, Masitah (International Journal of Law Reconstruction, 2023)
This research is based on legal problems against workers who work overtime, which is not in accordance with labor laws and regulations. The problems raised in this study are how legal protection for workers who work over the overtime limit based on labor law and obstacles in the implementation of legal protection for workers who exceed the overtime limit based on labor law. The purpose of this study is to determine the legal protection of workers who work overtime based on labor law and obstacles in the implementation of legal protection for workers who exceed overtime working time limits. This research uses descriptive analytical research methods, the approach used is normative juridical. The approach method used in this research is the statute approach. The implementation of legal protection for workers who exceed the working time limit has not been fully implemented based on Article78 letter b, namely overtime working time which can only be done at a maximum of 3 hours in 1 day and 14 hours in 1 week. The inhibiting factors are the lack of maximum worker performance in carrying out a job and the lack of labor owned by the company.